Induction, establishment in vitro, and characterization of functional, antigen-specific, carrier-primed murine T-cell lymphomas. - Finn, O J (1979)
T cells were isolated from spleens of C57BL/Ka/Thy 1.1/Lb mice immunized with 2,4-dinitrophenylated keyhole limpet hemocyanin (DNP-KLH). The mice were infected in vitro with radiation leukemia virus and injected intrathymically into congenic C57BL/Ka (Thy 1.2) recipients. Within 3-4 months, seven thymic lymphomas developed, five of which were of donor type. The donor lymphomas were explanted and permanent cell lines were established in vitro. These lymphoma cells are capable of providing antigen-specific carrier (KLH)-primed help to DNP-primed B lymphocytes in secondary antibody production to DNP-KLH. They also enhance the secondary antibody response of whole period spleen cell populations to DNP-KLH. The availability of these immortal clonable populations of immunofunctional neoplastic T lymphocytes should facilitate biological and biochemical investigations of lymphocyte interactions during synthesis of antibody to thymus-dependent antigens.